Obtaing the powder of the bark from Ziziphus Joazeiro Mart. by foam-mat drying (Research, Society and Development, 2021)
The juazeiro (Ziziphus joazeiro Mart.), is a tree found in the semiarid region of Northeast Brazil and is considered a notable representative of the Caatinga. It has several applications, and a high saponin content. Therefore, the objective of this work was to study the drying in a foam layer (foam-mat drying) of the Ziziphus joazeiro bark for later obtaining the powder. The influence of the following variables was studied: drying temperature, stirring time and juazeiro concentration, on the final drying time of the bark. And the physical characteristics of the formed foam were evaluated: stability, density, expansion and incorporation of air. The physicochemical characterization of the powder obtained was also carried out through the following analyses: water activity; solubility; soluble solids content; pH and NMR spectra. The foams showed good stability; the density decreased with the concentration of juazeiro and with the time of agitation; greatest incorporation of air for the experiment with the longest stirring time. In drying, the only variable with a statiscally significant influence on the 95% confidence interval fot the final drying time was temperature. The values of water activity of the powde and pH were considered in the acceptable range, the soluble solids content of the powder obtained was considered low. It was not possible to identify the characteristic signals of saponins in the NMR spectra. Therefore, it is concluded that drying in a foam layer proved to be a satisfactory and viable method to obtain powdered of the bark from Ziziphus joazeiro, and the powder obtained showed characteristics that point to it as a good foaming agent.